2017
DOI: 10.1021/acs.jcim.7b00128
|View full text |Cite
|
Sign up to set email alerts
|

Privileged Structural Motif Detection and Analysis Using Generative Topographic Maps

Abstract: Identification of "privileged structural motifs" associated with specific target families is of particular importance for designing novel bioactive compounds. Here, we demonstrate that they can be extracted from a data distribution represented on a two-dimensional map obtained by Generative Topographic Mapping (GTM). In GTM, structurally related molecules are grouped together on the map. Zones of the map preferentially populated by target-specific compounds were delineated, which helped to capture common subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…However, it should work in cases where people intend to exploit the chemical similarity principle . Or, as our peers would say, the data set must be neighborhood behavior-compliant , for the method to work.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should work in cases where people intend to exploit the chemical similarity principle . Or, as our peers would say, the data set must be neighborhood behavior-compliant , for the method to work.…”
Section: Discussionmentioning
confidence: 99%
“…Molecules with the same RPs are considered to belong to a same cluster or “family”, because they share some common structural motif which is the underlying reason for their mapping into the same map zone “covered” by the RP. As already shown, common structural motifs may range from precisely defined scaffolds or even specifically substituted scaffolds, to fuzzier ensembles of related, interchangeable scaffolds, to even fuzzier “pharmacophore‐like” patterns.…”
Section: Methodsmentioning
confidence: 99%
“…Projecting the multidimensional items (molecules for which high-dimensional descriptor elements each capture specific structural features) onto a two-dimensional (2D) latent grid is expected to mechanically reduce the predictive power, compared to any ideal machine learning method that operates in the original descriptor space. Nevertheless, previous studies ,, have typically shown that GTM-driven classification or regression models are on par or only slightly less predictive than equivalent support vector machine or random forest approaches.…”
Section: Introductionmentioning
confidence: 96%
“…Like any global maps, their resolution is expectedly lower than the one that could be achieved by dedicated GTMs, focusing on specific series of compounds. The key question addressed in this work is whether such global maps, primarily conceived to serve as a rather coarse-grained “atlas” of the various structural motifs explored in to-date medicinal chemistry, ,, may nevertheless be successfully exploited as an accurate virtual screening and property prediction tool. This is envisaged by means of a consensus predictor using several universal maps, built on distinct initial descriptor spaces capturing distinct chemical information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation